POTENSI EKONOMI SEKTOR PERTANIAN, KEHUTANAN DAN PERIKANAN KABUPATEN MERANGIN - Silvia Rahayu (Gapenas Publisher, 2022)
This study aims to examine the economic potential in the sector and sub-sector of agriculture, forestry and fisheries of Merangin Regency. To identify and determine the leading agricultural, forestry and fisheries sub-sectors in Merangin District. From the results of the research, it is obtained that the economic potential in the sector and sub-sector of agriculture, forestry and fisheries of Merangin Regency based on the results of the calculation of the Shift Share obtained the largest value, namely Proportionality Shift, which reaches Rp. 4,612,628.26 (50.18%) which means that the economic structure of the Regency Merangin is quite large due to the component of economic growth from within the region itself from the total component of the Shift share. Thus, it can be seen that the factors that influence and determine the potential for economic growth of Merangin Regency in 2015-2019 are influenced and determined by the components of economic growth from within the region itself which is caused by the relatively good regional economic structure, namely specialized in sectors that are nationally can fast growth like the industrial sector. Based on the LQ calculation, the leading agriculture, forestry and fisheries sub-sectors in Merangin Regency include the agriculture, livestock, hunting and agricultural services sub-sector (1st place), the forestry and logging sub-sector (2nd place) and the fisheries sub-sector (3rd place). The three agricultural subsectors in Merangin District have LQ> 1 values.